2013
DOI: 10.1080/10410236.2013.795645
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Youth Health in Primary Care: Lessons Learned From General Practitioners

Abstract: Primary care represents a fundamental component of the health system, particularly for young people. However, youth access to primary care is less than ideal. To optimize clinician capacity to promote youth health, an interactive training module was developed and tailored to the needs of general practitioners. As part of an exploratory study, 11 participants were interviewed to determine the perceived capacity of the module to promote youth-friendly primary care. Findings suggest the module can enhance clinici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…[8][9][10][11][12] Youth healthcare can be a challenging area to work, partly because of limited support. [13][14][15][16] A systematic review suggested youth access to sexual and reproductive health services is hindered by service accessibility; privacy and confidentiality; and staff characteristics and competencies. 17 Another concluded that youth engagement with health systems is influenced by "the ability to recognize and understand health issues; service knowledge and attitudes toward help-seeking; structural barriers; professionals' knowledge, skills, attitudes; service environments and structures; ability to navigate the health system; youth participation; and technology opportunities".…”
Section: Youth Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12] Youth healthcare can be a challenging area to work, partly because of limited support. [13][14][15][16] A systematic review suggested youth access to sexual and reproductive health services is hindered by service accessibility; privacy and confidentiality; and staff characteristics and competencies. 17 Another concluded that youth engagement with health systems is influenced by "the ability to recognize and understand health issues; service knowledge and attitudes toward help-seeking; structural barriers; professionals' knowledge, skills, attitudes; service environments and structures; ability to navigate the health system; youth participation; and technology opportunities".…”
Section: Youth Healthmentioning
confidence: 99%
“…Youth healthcare can be a challenging area to work, partly because of limited support . A systematic review suggested youth access to sexual and reproductive health services is hindered by service accessibility; privacy and confidentiality; and staff characteristics and competencies .…”
Section: Introductionmentioning
confidence: 99%
“…Studies among health professionals have found that young people in general are perceived as challenging. Clinicians often can lack skills and confidence to engage young people (Gearing et al, 2012) or require more time to manage some health and psychosocial issues (Dadich et al, 2014; Jarrett et al, 2011). Some clinicians do not always see it as their role to provide comprehensive and coordinated care for young people (Dadich et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Like many other nations, Australia is witnessing ‘the single biggest health reform in a quarter of a century’, the essence of which is health care that is ‘funded nationally … and run locally’ . Given mounting evidence on what works in youth health care, current health reforms represent a window of opportunity to promote youth health.…”
mentioning
confidence: 99%
“…and run locally'. 27 Given mounting evidence on what works in youth health care, 28,29 current health reforms represent a window of opportunity to promote youth health.…”
mentioning
confidence: 99%